2017
DOI: 10.2337/dc17-1025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Telemedicine Follow-up Care on Diabetes-Related Foot Ulcers: A Cluster-Randomized Controlled Noninferiority Trial

Abstract: The results suggest that use of TM technology can be a relevant alternative and supplement to usual care, at least for patients with more superficial ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(143 citation statements)
references
References 28 publications
1
135
0
7
Order By: Relevance
“…73 A lower proportion of patients with an amputation was found in the telemedicine group (−8.3%, 95%CI: −16.3 to 0.5%). 73 Based on this RCT, four qualitative studies investigated the value of focus groups and individual semi-structured interviews of both patients and healthcare professionals. [74][75][76][77] Patients from both the telemedicine and the control group mentioned that the best wound care depends on a combination of competence and professional skills in wound management and continuity of care.…”
Section: Rct Wilbright Et Al Reported No Significant Difference In Umentioning
confidence: 85%
See 4 more Smart Citations
“…73 A lower proportion of patients with an amputation was found in the telemedicine group (−8.3%, 95%CI: −16.3 to 0.5%). 73 Based on this RCT, four qualitative studies investigated the value of focus groups and individual semi-structured interviews of both patients and healthcare professionals. [74][75][76][77] Patients from both the telemedicine and the control group mentioned that the best wound care depends on a combination of competence and professional skills in wound management and continuity of care.…”
Section: Rct Wilbright Et Al Reported No Significant Difference In Umentioning
confidence: 85%
“…Recently, Smith‐Strøm et al found in a cluster randomized controlled noninferiority trial that weekly telemedicine consultations of the community nurse via an interactive Web‐based ulcer record and a mobile phone that enabled counseling and communication with the healthcare specialist in addition to outpatient clinic every 6 weeks, was non‐inferior to visiting the outpatient clinic every second week for ulcer treatment on time to healing (mean difference −0.43 months [95%CI: −1.50 to 0.65]) . A lower proportion of patients with an amputation was found in the telemedicine group (−8.3%, 95%CI: −16.3 to 0.5%) . Based on this RCT, four qualitative studies investigated the value of focus groups and individual semi‐structured interviews of both patients and healthcare professionals .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations